2003
DOI: 10.1038/sj.mp.4001313
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal mechanism of nociceptin-induced modulation of learning and memory: Involvement of N-methyl-D-aspartate receptors

Abstract: Nociceptin (also called orphanin FQ) is an endogenous heptadecapeptide that activates the opioid receptor-like 1 (ORL 1 ) receptor. Nociceptin system not only affects the nociception and locomotor activity, but also regulates learning and memory in rodents. We have previously reported that long-term potentiation and memory of ORL 1 receptor knockout mice are enhanced compared with those in wild-type mice. Here, we show the neuronal mechanism of nociceptin-induced modulation of learning and memory. Retention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 53 publications
(82 reference statements)
8
53
1
Order By: Relevance
“…These findings strongly suggest that the NOP receptor agonist selectively interferes with mnemonic processes related to long-term consolidation processes. This is in line with previous studies showing that N/OFQ abolishes long-term retention of fear conditioning and passive avoidance when administered post-training (Mamiya et al, 2003;Roozendaal et al, 2007). Interestingly, when injected into the dorsal hippocampus, N/OFQ severely impaired long-term recognition memory formation, without any apparent effects on sensorimotor functions.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…These findings strongly suggest that the NOP receptor agonist selectively interferes with mnemonic processes related to long-term consolidation processes. This is in line with previous studies showing that N/OFQ abolishes long-term retention of fear conditioning and passive avoidance when administered post-training (Mamiya et al, 2003;Roozendaal et al, 2007). Interestingly, when injected into the dorsal hippocampus, N/OFQ severely impaired long-term recognition memory formation, without any apparent effects on sensorimotor functions.…”
Section: Discussionsupporting
confidence: 79%
“…N/OFQ and its receptor are densely expressed in brain regions associated with learning and memory processes, such as the hippocampus, the amygdala, and the cerebral cortex (Darland and Grandy, 1998;Neal et al, 1999a,b). Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations